Tanggung Jawab Notaris dalam Kewenangannya Melakukan Legalisasi Perjanjian di Bawah Tangan - Ninik Darmini (University of Udayana, 2023)
rivate deed legalization is a Notary’s authority to serve the community based on the Notary Act. Legalization that is conducted without good faith and circumspection could bring a Notary into trouble. This research aims to understand and analyze the liability of a Notary in private deed legalization. This descriptive doctrinal legal research uses secondary data that is supported by primary data which were then analyzed qualitatively. This research concludes that, first, legalization by a Notary who by his/her mistake causes harm to another party consequently brings administrative, civil, and/or criminal liability. The administrative liability is based on Article 16 paragraph (1) letter a jis. Article 16 paragraph (11), and 73 paragraph (1) letter e of the Notary Act; the civil liability is based on Article 1365 of the Indonesian Civil Code on civil wrongdoing; while the criminal liability is based on Article 55 of the Indonesian Criminal Code on deelneming and Article 263 on document falsification. Second, good faith ought to be a Notary’s guidance in carrying out his/her position as it would prevent him/her from either administrative, civil, or criminal sanctions. Third, it is necessary for a Notary to apply circumspection by not getting involved in the contract-making of the private deed; observing the private deed contents to ensure that it is not against the law; and documenting the legalization properly, although a legalization is passive in nature. galisasi perjanjian di bawah tangan merupakan kewenangan Notaris yang diatur dalam Undang-Undang Jabatan Notaris. Legalisasi yang dilakukan tanpa itikad baik dan kehati-hatian dapat membawa Notaris ke dalam masalah. Penelitian ini bertujuan untuk memahami dan menganalisis tanggung jawab Notaris dalam legalisasi perjanjian di bawah tangan. Penelitian hukum normatif yang bersifat deskriptif ini menggunakan data sekunder yang didukung dengan data primer, kemudian dianalisis secara kualitatif. Penelitian ini menemukan bahwa, pertama, legalisasi oleh Notaris yang oleh karena kesalahannya merugikan pihak lain berakibat pada pertanggungjawaban secara administratif, perdata, dan/atau pidana. Pertanggungjawaban administratif didasarkan pada Pasal 16 ayat (1) huruf a jis. Pasal 16 ayat (11) dan Pasal 73 ayat (1) huruf e UU Notaris; pertanggungjawaban perdata didasarkan pada Pasal 1365 KUHPerdata tentang Perbuatan Melawan Hukum; sedangkan pertanggungjawaban pidana didasarkan pada Pasal 55 KUHP tentang deelneming dan Pasal 263 KUHP tentang pemalsuan dokumen. Kedua, Notaris harus berpegang pada itikad baik dalam melaksanakan jabatannya karena hal tersebut dapat mencegahnya dari pengenaan sanksi administratif, perdata, maupun pidana. Ketiga, sangat penting bagi Notaris untuk menerapkan kehati-hatian meskipun legalisasi bersifat pasif, dengan tidak terlibat pada pembuatan perjanjian di bawah tangan; mengamati substansi perjanjian tersebut untuk memastikan tidak ada pertentangan dengan hukum; dan mendokumentasikan legalisasi dengan baik.